Isolation, Multiplication, and Characterization of Arbuscular Mycorrhizal Fungi Strains in Soils of North-East Morocco: Impact of Soils and Trap Plants - Chafai Wissame; El Yeznasni Hanae; Khalid Ahmed (E3S Web of Conferences)
This study, carried out in the eastern region of Morocco, aims to valorize and isolate indigenous arbuscular mycorrhizal fungi (AMF) from four soils (Guercif, Zaïo, Berkane and Bouarg). These strains, which are adapted to the harsh climatic and soil conditions of the region, were capturedand propagated using two host plants (Allium porrum and Hordeum vulgare). A multistage protocol was used for the isolation and propagation of AMF. Results showed that mycorrhizal colonization of leek roots during trapping was highest in Guercif soil, reaching 90 and 70% mycorrhizal frequency and intensity, respectively, while Berkane soil had the lowest values. This trend was also observed in barley, but with lower colonization values than in leeks. The evaluation of AMF richness revealed a higher abundance of AMF species in the rhizospheres of leek roots than in those of barley. The first propagation of AMF strains allowed the maintenance of certain species, but the second step led to the loss of some of these species. However, the third propagation step preserved all AMF stains. Further studies are needed to evaluate the efficacy of these indigenous AMF species in the field and under different environmental conditions. The application of these indigenous AMF species as biofertilizers could offer significant benefits for the promotion of sustainable agriculture in Moroccan ecosystems.